REAL-TIME IMPLEMENTATION OF AN OVERHEAD POWER LINE CABLE SAG MONITORING SYSTEM (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2024)
This paper presents a calculation method and a real-time monitoring system for overhead power line cable sag, following the increased need over the last decade to accurately estimate its value. Thus, the hardware/software architecture of such a system is presented, which uses in addition to the geometrical data of the power line, the information provided by a specialized sensor to measure the horizontal mechanical tension in the cable. Based on the catenary equation, numerical simulations implemented in Matlab environment are presented to obtain the value of the overhead power transmission line cable sag. Real-time software implementation in Laboratory Virtual Instrument Engineering Workbench (LabVIEW) programming environment of overhead power line condition monitoring is also presented.
Keywords: Remote monitoring; Real time; Sag calculus